A method of plotting two variables (such as mean incidence and variability from year to year) on the same map, using isopleths - Learmonth, Andrew Thomas Amos; Pal, Manindra Nath (ERDKUNDE, 1959)
An earlier paper described a method of combined plotting of two mutually dependent variables on a choropleth map; this method has since been modified by the Regional Survey Unit of the Indian Statistical Institute for application to an isopleth map with two variables. The method is demonstrated with three examples: 1. Figures 1 a and 1 b compare a choropleth and an isopleth map of average cholera deaths and their year-to-year variation for the 82 talukas (lower administrative units) of the former state of Mysore. As in all other examples, the choice of hatching type was made after a prior examination of frequency and any conspicuous spatial distribution. The level of fatalities is represented by density of hatching and thickness of lines, and the extent of variation is represented by the direction of hatching. The isolines were interpolated in the usual manner from height numbers placed at the geometric center of each administrative unit. The unit of measure of variation chosen depended on the study; in this case, it was the absolute average variation (expressed in %) relative to the average number of deaths. Both maps are instructive in showing the contrast between endemic areas with a relatively constant number of deaths and epidemic areas with large fluctuations in their numbers. The choropleth map is more honest in that it is clear from it to which spatial units the numbers refer. The isopleth map has the advantage of showing spatial trends in an almost three-dimensional way. Following the maps, an attempt is made to interpret the distribution patterns revealed by them. Figures 2a and 2b are two maps in a series showing the monthly mean of precipitation and its variation over a thirty-year period. The measure of variation chosen was the percentage of the quarterly interval, i.e., half the distance between the upper and lower quarters, relative to the average precipitation at each of the 145 observation stations used. The series of maps as such has been used for a preliminary determination of areas of varying rainfall character. It is hoped that it will stimulate the demand for the preparation of maps showing the moisture requirements of certain crops throughout the year, so that general conclusions can be drawn as to which areas should be advised to grow a particular crop by organs of agricultural education and extension. Figure 3 is a map showing the average yield of ragi ( eleusine corocana) and the deviations from the average. It is based on examples taken in selected villages, with villages grouped by talukas in the former state of Mysore. The measure of deviation chosen in this case was the average absolute deviation in value yield. This map gave the extremely interesting indication that in the central area of market cultivation yields are uniform but quite low, while in the outlying areas there is a tendency toward high but fluctuating yields.